Phytochemicals and Antioxidant Activity of the Almond Kernel (Prunus dulcis Mill.) from Turkey - Keser, Serhat; Demir, Ersin; Yilmaz, Okkes (Chem Soc Pakistan, 2014)
Almond belong to Rosaceae family and it is a rich source of nutrients because of phytochemicals including phenolic compounds, phytosterols, flavonoids, phenolic acids, vitamins and fatty acids. In this study, we determined antioxidant activities and phenolic, flavonoid, phytosterol, lipid soluble vitamin and fatty acid contents of almond kernel extract. Antioxidant activity of almond extract was investigated by DPPH center dot, ABTS(center dot+), OH center dot radical scavenging, metal chelating activity and determination of lipid peroxidation levels (TBARS). Almond extract scavenged 89.50% of the ABTS radical, 66.77% of the hydroxyl radical, and 87.30% of the DPPH radical. This extract showed 72.05% of the metal chelating activity. Kaempferol (223.54 mu g/g), naringenin (5.01 mu g/g), vanillic acid (110.89 mu g/g), caffeic acid (65.72 mu g/g) and ferulic acid (16.49 mu g/g) were determined in the almond extract. The major fatty acids were oleic acid (76.23%) and linoleic acid (15.43%). delta-tocopherol (3.05 mg/kg), alpha-tocopherol (104.40 mg/kg), and vitamin K (38.25 mg/kg) were determined in the almond extract. These results indicate that almond extract is a good natural source of fatty acids, lipid soluble vitamins, phytosterols, flavonoid, phenolic compounds. In addition, these findings are important for the nutrition sciences, because fatty acids, lipid soluble vitamins, phytosterols, flavonoid, phenolic compounds and antiradical properties, in particular, seem to have considerable effect on health.
Keywords: Almond; DPPH; ABTS; Fatty acid; Flavanoid; Vitamin and Phytosterol